Large bore natural gas engine performance improvements and combustion stabilization through reformed natural gas precombustion chamber fueling - Ruter, Matthew D., author; Olsen, Daniel B., advisor; De Miranda, Michael A., committee member; Marchese, Anthony John, 1967-, committee member (Colorado State University. Libraries, 2010)
Lean combustion is a standard approach used to reduce NOx emissions in large bore natural gas engines. However, at lean operating points, combustion instabilities and misfires give rise to high total hydrocarbon (THC) and carbon monoxide (CO) emissions. To counteract this effect, pre-combustion chamber (PCC) technology is employed to allow engine operation at an overall lean equivalence ratio while mitigating the rise of THC and CO caused by combustion instability and partial and complete misfires. A PCC is a small chamber, typically 1-2% of the clearance volume. A separate fuel line supplies gaseous fuel to the PCC and a standard spark plug ignites the slightly rich mixture (1.1 < Φ < 1.2) in the PCC. The ignited PCC mixture enters the main combustion chamber as a high energy flame jet, igniting the lean mixture in the main chamber. Typically, natural gas fuels both the main cylinder and the PCC. In the current work reported herein, a mixture of reformed natural gas (syngas) and natural gas fuels the PCC. Syngas is a broad term that refers to a synthetic gaseous fuel. In this case, syngas specifically denotes a mixture of hydrogen, carbon monoxide, nitrogen, and methane generated in a natural gas reformer. Syngas has a faster flame speed and a wider equivalence ratio range of operation. Fueling the PCC with syngas reduces combustion instabilities and misfires. This extends the overall engine lean limit, enabling further NOx reductions. Research results presented are aimed at quantifying the benefits of syngas PCC fueling. A model is developed to predict the equivalence ratio in the PCC for different mixtures and flow rates of PCC fuel. An electronic injection valve is used to supply the PCC with syngas. The delivery pressure, injection timing, and flow rates are varied to optimize PCC equivalence ratio. The two syngas mixtures evaluated contain the same ratio of hydrogen to carbon monoxide but different levels of nitrogen diluent. The syngas with the higher nitrogen content is denoted syngas 1 while syngas 2 specifies the lower nitrogen content syngas. Experimental results are presented for 80% syngas / 20% natural gas mixtures for each syngas PCC fueling scenario at 18" Hg intake manifold pressure. 80% syngas 1 / 20% natural gas PCC fueling resulted in an 18% reduction in NOx emission compared to natural gas fueling. Supplying the PCC with 80% syngas 2 / 20% natural gas improves combustion stability by 16% compared to natural gas PCC fueling. Increasing the intake manifold pressure to 22" Hg for 80% syngas 2 / 20% natural gas fueling provides an emission comparison at an equivalent combustion stability operating point. Comparing equivalent combustion stability operating points between syngas 2 and natural gas shows a 40% reduction in NOx emissions when fueling the PCC with 80% syngas 2 / 20% natural gas mixture compared to natural gas fueling. Experimental results are presented for varying PCC fuel mixtures of syngas 2 and natural gas at 18" Hg intake manifold pressure. Results show dramatic increases in combustion stability are realized for high syngas 2 mixtures (greater than 80% syngas 2). Reducing intake manifold boost for natural gas PCC fueling to 8.5" Hg produces equivalent main cylinder combustion stability compared to 100% syngas 2 PCC fueling at 18" Hg intake manifold pressure. NOx emission increases by 780% for natural gas PCC fueling at the equivalent combustion stability operating point compared to syngas 2 PCC fueling at 18" Hg intake manifold pressure.
Keywords: reformed natural gas; combustion stabilization; pre-combustion chamber; large bore natural gas; Synthetic fuels; Natural gas; Internal combustion engines; Spark ignition engines -- Alternative fuels; Syngas